Efektivitas Pelatihan Asertivitas untuk Meningkatkan Perilaku Asertif Siswa Korban Bullying - Akhmad Rifqi Azis (Indonesian Institute for Counseling, Education and Therapy (IICET), 2015)
Bullying a concrete impact on the victim both physically and psychologically. The main characteristics of bullying victims is students who have not been able to be assertive. To improve the student assertive behavior bullying victim, the counselor can use assertiveness training. The purpose of this research was to know the effectiveness of assertiveness training to improve the student assertive behavior bullying victim. This research uses a pure experimental design pretest-posttest control group design. The research population was a 8 student of class VII & VIII SMPN1 Jombang - Jember who are bullying victims. The data analysis used Two independent sample test man withney U. These results indicate that statistic score of Z (-2.323) and sig.(2-tailed) is 0.020 <0.05, So assertiveness training effective to improve assertive behavior student bullying victims. Suggestions of the researchers as follows: 1) for the instution of the school should give counselor should gives assertiveness training to improve the student assertive behavior bullying victims. 2) for the counselor be creative for improve assertive training module. And 3) for other researcher should use time series design and broad population so that get good generality broader.